Use of fungi in bioremediation of pesticides - Fragoeiro, Silvia (Cranfield University, 2005)
Eight isolates (7 species) of white rot fungi were grown on soil extract agar amended with 0, 5 10 and 20 mg l- simazine, trifluralin and dieldrin, individually and as a mixture, under two different water regimes (-0.7 and -2.8 MPa water potential). The best isolates were T.versicolor (R26 and R101) and P.ostreatus, exhibiting good tolerance to the pesticides and water stress and the ability to degrade lignin and produce laccase in the presence of these pesticides. As a result, the activity of those three isolates plus Phanerochaete chrysosporium (well described for its bioremediation potential) was examined in soil extract broth in relation to differential degradation of the pesticide mixture at different concentrations (0-30 mg l-1) under different osmotic stress levels (-0.7 and -2.8 MPa). Enzyme production, relevant to P and N release (phosphomonoesterase, protease), carbon cycling (β-glucosidase, cellulase) and laccase, involved in lignin degradation was quantified. The results suggested that the test isolates have the ability to degrade different groups of pesticides, supported by the capacity for expression of a range of extracellular enzymes at both -0.7 and -2.8 MPa water potential. P.chrysosporium and T.versicolor R101, were able to degrade this mixture of pesticides independently of laccase activity, whereas P.ostreatus and T.versicolor R26 showed higher production of this enzyme. Complete degradation of dieldrin and trifluralin was observed, while about 80% of the simazine was degraded regardless of osmotic stress treatment in a nutritionally poor soil extract broth. The results with toxicity test (Toxalert®10), suggested the pesticides were metabolised. Therefore the capacity for the degradation of high concentrations of mixtures of pesticides and the production of a range of enzymes, even under osmotic stress, suggested potential applications in soil. Subsequently, microcosm studies of soil artificially contaminated with a mixture of pesticides (simazine, trifluralin and dieldrin, 5 and 10 mg kg soil-1) inoculated with P.ostreatus, T.versicolor R26 and P.chrysosporium, grown on wood chips and spent mushroom compost (SMC) were examined for biodegradation capacity at 15ºC. The three test isolates successfully grew and produced extracellular enzymes in soil. Respiratory activity was enhanced in soil inoculated with the test isolates, and was generally higher in the presence of the pesticide mixture, which suggested increased ii mineralization. Cellulase and dehydrogenase was also higher in inoculated soil than in the control especially after 12 weeks incubation. Laccase was produced at very high levels, only when T.versicolor R26 and P.ostreatus were present. Greatest degradation for the three pesticides was achieved by T.versicolor R26, after 6 weeks with degradation rates for simazine, trifluralin and dieldrin 46, 57, and 51% higher than in natural soil. And by P.chrysosporium, after 12 weeks, with degradation rates 58, 74, and 70% higher than the control. The amendment of soil with SMC also improved pesticide degradation (17, 49 and 76% increase in degradation of simazine, trifluralin and dieldrin compared with the control).